Association of time‐varying clearance of nivolumab with disease dynamics and its implications on exposure response analysis. Issue 5 (22nd March 2017) - Liu, C; Yu, J; Li, H; Liu, J; Xu, Y; Song, P; Liu, Q; Zhao, H; Xu, J; Maher, VE; Booth, BP; Kim, G; et al.
Abstract : Nivolumab is a human monoclonal antibody that blocks the interaction between PD‐1 programmed death‐1 (PD‐1) and its ligands, PD‐L1 and PD‐L2. Nivolumab demonstrated efficacy in clinical trials for various types of cancer. A time‐varying clearance was identified for nivolumab. We show that the change of clearance over time is associated with the post‐treatment effects: clearance decreases when disease status improves. This interaction between posttreatment effects and drug exposure may lead to a biased steep estimate of the exposure–response (E‐R) relationship for efficacy. Under this scenario, simulations were performed to develop a proposed methodology to assess the causal effect of drug exposure upon clinical response. Data from nivolumab trials were subsequently used to verify the proposed methodology for E‐R analysis. The results showed that E‐R analysis results based on pharmacokinetic (PK) metrics derived from the first dose are more consistent with the true E‐R or dose–response relationship than the steady‐state PK metrics.